From corporate tax competition to global cooperation? Trends, prospects and effects on German family businesses - Anna Theresa Bührle; Katharina Nicolay; Christoph Spengel; Sophia Wickel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This study provides an overview of current political developments in the tax competition debate, emphasizing the consequences for large German family businesses. We analyze new tax competition trends in Europe and selected industrialized countries in recent years. Subsequently, we discuss various international tax policy counter-reactions, namely the Anti-Tax Avoidance Directive and country-by-country reporting on the European level as well as the OECD's two-pillar project. We outline a potential shift in tax competition away from companies towards highly wealthy and highly qualified individuals. The implications of these developments on large German family businesses are emphasized, offering insights into the evolving landscape of tax competition.
Keywords: H25; H24; K34; 330; tax competition; family businesses; international tax policy